2016
DOI: 10.1177/1538574415625813
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Endovenous Laser and Radiofrequency Ablation in Treating Varicose Veins in the Same Patient

Abstract: The EVLA procedure may be superior to RFA in certain respects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
3
10
1
Order By: Relevance
“…In early period of our RFA practice, we recommended enoxaparin for a week in the postoperative period and aspirin for a month, therefore the rate of ecchymosis was high in our series. However, our rate of ecchymosis was no higher than previous published studies, and a cure was achieved within two weeks [3,9,11] and we no longer administer this medication. Although DVT prevalence after RFA is believed to be between 0.2% and 1% [15], we did not observe any acute thrombosis or DVT in present study.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…In early period of our RFA practice, we recommended enoxaparin for a week in the postoperative period and aspirin for a month, therefore the rate of ecchymosis was high in our series. However, our rate of ecchymosis was no higher than previous published studies, and a cure was achieved within two weeks [3,9,11] and we no longer administer this medication. Although DVT prevalence after RFA is believed to be between 0.2% and 1% [15], we did not observe any acute thrombosis or DVT in present study.…”
Section: Discussioncontrasting
confidence: 60%
“…Eroğlu et al did not reveal a difference in their randomized controlled study comparing cyanoacrylate, RFA and EVLA procedures in respect to 2-year occlusion rates (occlusion rates were 92.6%, 90.9%, 91.5% respectively) (3). Bozoğlan et al reported that the occlusion rates in their study that compare EVLA and RFA procedures, were respectively 100% and 94% after 6 months of follow-up [9]. In the study of 155 patients treated with RFA, Shepherd et al reported 94.1% occlusion rate after an average follow-up of 12.2 months [10].…”
Section: Discussionmentioning
confidence: 99%
“…There is only one study in the literature comparing RFA with current laser catheters. Bozoglan et al used RFA and 1470 nm radial fiber laser catheter in two different extremities of the same patient and reported that EVLA was superior to RFA in terms of postoperative pain and rate of return to daily activity [ 9 ]. Our findings are not compatible with this study.…”
Section: Resultsmentioning
confidence: 99%
“…Because of this, new studies are needed with the use of new generation catheters with high wave length and new tip designs. Advances in laser catheters may alter the results and end the superiority of the RFA [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…EVTA is technically more challenging than USGS; however, several studies have shown highly effective and durable closure rates, with closure rates ranging between 61% and 95% (37)(38)(39)(40). A recent comparison between minimally invasive techniques for perforator ablation showed EVTA had better early closure rates when compared to USGS; however, this rate narrowly missed significance (40).…”
Section: Evtamentioning
confidence: 96%